‘Petrarch’s Sonnets’ by Liszt - Nowik, Wojciech (Interdisciplinary Studies in Musicology, 2018)
The article ‘Petrarch’s Sonnets’ by Liszt revolves around the phenomenon of transformation, which dominated F. Liszt’s works. His impressive composing achievements made Liszt an unequalled author of all types of elaborations, paraphrases, adaptations, transcripts of both his own and other composer’s works, representing various styles and epochs. What is more, the transformation techniques employed by Liszt, different from the commonly applied evolutionary ones, coupled with extended tonality and harmony as well as new textures, resulted in an extremely broad scale of expression and subtly diverse expressive effects. Three of Petrarch’s Sonnets from the Rerum vulgarium fragmenta collection are dedicated to Laura and represent this article’s major area of interest. The Hungarian composer worked on them three times: twice he composed them as songs and once as a piano triptych included in the Années de Pèlerinage. Dèuxieme Année: Italie series. His interpretation of the Sonnets, as well as the remaining works in the series, was inspired by the art of the old Italian masters married with the Romantic idea of correspondence des artes. While it is a part of artistic tradition to turn poetic works into songs (resulting in the vocal lyrics so typical of Romanticism), adding a musical dimension to a sonnet, a piece of poetry with a specific organisation of its content, a unique form and verse discipline, seems risky. It is extremely difficult to successfully transfer equivalent themes and structures onto a different medium i.e. piano music. By turning to Petrarch’s Sonnets, Liszt created congenial palimpsests, reflecting the syntactical and formal rudiments of the verse but, first and foremost, managing to portray Laura in new incarnations, subtly changing in the eternal search for the ideal of femininity, the so-called “Ewig-weibliche”. Especially in the piano version, Liszt seems to have accomplished the esoteric subtlety of the “Sprache über Sprache” available to and understood solely by poets and those in the know.